Impact of eaves on cross-ventilation of a generic isolated leeward sawtooth roof building: Windward eaves, leeward eaves and eaves inclination. (October 2015) - Perén, J.I.; van Hooff, T.; Leite, B.C.C.; Blocken, B.
Abstract: An eaves is a roof extension that can protect the indoor environment from direct solar radiation, the exterior facade from wetting of by wind-driven rain and can be useful to enhance cross-ventilation. This paper evaluates the impact of eaves configuration on wind-driven cross-ventilation of a generic leeward sawtooth roof building. Both the type of eaves (windward versus leeward) and the eaves inclination angles are investigated. Isothermal Computational Fluid Dynamics (CFD) simulations are performed using the 3D steady Reynolds-Averaged Navier–Stokes (RANS) approach. A grid-sensitivity analysis is performed and validation of the CFD results is conducted based on wind-tunnel measurements with Particle Image Velocimetry from literature. The ventilation evaluation is based on the volume flow rates and the indoor mean velocities. The eaves length is 1/4 of the building depth and the inclination is varied between 90° and −45° for both the windward and leeward eaves. The results show that windward eaves with an inclination of 27° (equal to roof inclination) result in the highest increase of the volume flow rate (15%) compared to the building without eaves. Furthermore, the flow through the occupied zone is more horizontally directed. Leeward eaves have a smaller influence on the ventilation volume flow rate than windward eaves; the maximum increase in volume flow rate is only 6% when a 90° inclination is employed. Application of both (windward and leeward eaves) results in an increase of the volume flow rate of 24%, which is 3% more than the sum of the increases by the two eaves separately. Graphical abstract: Highlights: CFD simulations of natural cross-ventilation flow with 3D steady RANS simulations. Influence of windward and leeward eaves on flow rate and velocity. Eaves have a large effect on the static pressure distribution on windward facade. Windward eaves have a much larger effect than leeward eaves. The angle of the eaves determines the effect on flow rate (increase or decrease).